1995
DOI: 10.21273/jashs.120.5.843
|View full text |Cite
|
Sign up to set email alerts
|

White-mold Avoidance and Agronomic Attributes of Upright Common Beans Grown at Multiple Planting Densities in Narrow Rows

Abstract: The putative yield advantage associated with growing upright beans (Phaseohs vulgaris L.) at high planting densities in narrow (0.23-m) rows might he compromised by a higher risk of white mold [Sclerotinia sclerotiorum (Lib.) de Bary] because of reduced air flow through the crop canopy. This four-yeai-study was undertaken to compare the white-mold avoidance and agronomic attributes of upright bean lines and to determine whether their yields can he i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 10 publications
2
28
0
1
Order By: Relevance
“…The lack of cultivars of different evolutionary origins with high levels of the monogenic white mold resistance has hampered the understanding of variation in virulence among pathogen isolates. Moreover, environmental effects and disease avoidance mechanisms (Ando et al, 2007; Coyne et al, 1974; Kolkman and Kelly 2002; Miklas et al, 2013; Saindon et al, 1995; Schwartz et al, 1987) often mask genetic differences for physiological resistance (Miklas and Grafton, 1992).…”
Section: The White Mold Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The lack of cultivars of different evolutionary origins with high levels of the monogenic white mold resistance has hampered the understanding of variation in virulence among pathogen isolates. Moreover, environmental effects and disease avoidance mechanisms (Ando et al, 2007; Coyne et al, 1974; Kolkman and Kelly 2002; Miklas et al, 2013; Saindon et al, 1995; Schwartz et al, 1987) often mask genetic differences for physiological resistance (Miklas and Grafton, 1992).…”
Section: The White Mold Diseasementioning
confidence: 99%
“…Integrated management strategies (Forster et al, 2000; Schwartz and Peairs, 1999) rely on a combination of approaches including fungicides, deep plowing, and long‐term crop rotations with nonhost crops such as corn ( Zea mays L.), small grain cereals, and sorghum [ Sorghum bicolor (L.) Moench]. White mold management practices such as use of wide‐row spacing and low plant populations, reduced irrigation and fertilizer, and use of upright cultivars with open plant canopy may reduce white mold severity and incidence (Ando et al, 2007; Coyne et al, 1974; Kolkman and Kelly, 2002; Schwartz et al, 1987); however, they also reduce common bean yield and the economic return to producers (Park, 1993; Saindon et al, 1995). Nonetheless, Peachery et al (2006) reported reduced white mold severity and increased pod yield in green bean due to increased‐row spacing.…”
Section: The White Mold Diseasementioning
confidence: 99%
“…Agronomic resistance, also known as “avoidance,” involves morphological traits that influence the micro‐environment of the host–microbe interaction. In beans, morphological resistance includes having an upright architecture to reduce humidity and moisture under the canopy, reduced days to flowering, and reduced time to maturity (Ando, Grumet, Terpstra, & Kelly, ; Kolkman & Kelly, ; Saindon, Huang, & Kozub, ). In contrast, physiological resistance is a biochemical or physical response to the pathogen, such as variation in photosynthetic rates and stomatal conductance.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate control of WM using fungicides and other disease management strategies has been difficult to achieve (del Río et al, 2004; Schwartz and Steadman, 1989), especially on the susceptible indeterminate prostrate growth habit Type III (Singh, 1982) dry bean cultivars that predominate in the western United States. Moreover, wide‐row spacing and low plant populations, reduced irrigation and fertilizer, and use of upright cultivars with open plant canopy may reduce WM severity and incidence; however, they also reduce dry bean yield and the economic return to producers (Park, 1993; Saindon et al, 1995).…”
mentioning
confidence: 99%